Consumers’ Awareness and Opinion Towards Food Adulteration in Selected Areas of West Bengal - Maiti, Madhurima (Indian Journal of Extension Education, 2022)
Food adulteration originated several decades ago and has become more prevalent day by day. The study was conducted in Kharagpur I block of West Medinipur district of West Bengal in 2017 and 2018 among 100 respondents to measure the level of awareness of adulteration through structured interview schedule. The study found that most of respondents, both in urban and rural areas of the study faced the problems of food adulteration. They lacked appropriate knowledge, tendencies and practices relating to food adulteration. Very few of them checked proper information in the packaging before buying. Based on the research this paper suggested that, to avoid the harmful consequences of adulteration, consumers must continuously develop a habit of upgrading their awareness level, develop a habit of checking the information printed in the package and try to adopt the best buying practices in order to keep themselves away from the hazardous consequences of food adulteration.
Keywords: Adulteration; Awareness; Buying practice; Consumer; Food; Food safety